Ultimate in-plane strengths of two-dimensional tri-axial braided composites: experiments and numerical simulations. (4th September 2019) - Wu, Jian; Rui, Yanjie; Ye, Wei; Ning, Huiming; Hu, Ning
The ultimate in-plane strengths of a carbon/glass fibre reinforced tri-axial braided composite are studied by experiments and numerical simulations. The ultimate tensile, compressible and shear strengths are tested. Employing Tsai-Wu failure criterion, a progressive failure analysis is performed in finite element analysis. Reasonable agreement between the experiments and numerical simulations indicates that present finite element model has a potential to predict the ultimate strengths of a two-dimensional tri-axial braided composite.